2012
DOI: 10.18388/abp.2012_2116
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling pathway and free radical impact.

Abstract: The activation of NF-κB transcription factor is critical for a wide range of processes such as immunity, inflammation, cell development, growth and survival. It is activated by a variety of stimuli including cytokines, ionizing radiation and oxidative stress. Redox modulations of NF-κB pathway have been widely demonstrated. Studies carried out during last years have advanced our knowledge about possible connections between NF-κB pathway and the impact of free radicals. This review is an endeavor to gather rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(103 citation statements)
references
References 83 publications
0
94
0
9
Order By: Relevance
“…The NF-kB transcription factor is down stream of the NF-kB signaling pathway that regulates genes involved in cell growth regulation, inflammation and other biological activities (Siomek, 2012). The signaling events that lead to NF-kB activation involve phosphorylation, ubiquitination, and proteolytic degradation of cytosolic IkB, followed by translocation of the active dimer (p65/p50) into the nucleus, where it binds to cognate DNA sequences to activate transcription of target genes (Barnes and Karin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The NF-kB transcription factor is down stream of the NF-kB signaling pathway that regulates genes involved in cell growth regulation, inflammation and other biological activities (Siomek, 2012). The signaling events that lead to NF-kB activation involve phosphorylation, ubiquitination, and proteolytic degradation of cytosolic IkB, followed by translocation of the active dimer (p65/p50) into the nucleus, where it binds to cognate DNA sequences to activate transcription of target genes (Barnes and Karin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigation has shown that dairy cows with ketosis exhibit oxidative stress during the transition period [12,18,20]. An imbalance in oxidants/antioxidants, an excess of oxidants and/or a depletion of antioxidants, can lead to oxidative stress, which mainly characterized by overproduction of ROS include superoxide anion (O 2 À ), hydroxyl radical (OH), and their molecular by-products (e.g., hydrogen peroxide H 2 O 2 ) in the body [15,41,42]. Overproduction of ROS has been closely related with oxidative stress, which is characterized with a major shift in the cellular redox balance and usually accompanied by ROS-mediated damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the transcription factor NF-kB is sequestered in the cytoplasm bound to its inhibitor IkBa, whose phosphorylation is dependent on IKKb activity. Once stimulated by some stimuli, NF-kB unit p65 separates from IkB and translocates into the nucleus where NF-kB can regulate the transcription of several inflammatory cytokines genes, for example tumor necrosis factor alpha (TNF-a), interleukin 6 (IL-6) and interleukin 1 beta (IL-1b) [13][14][15]. In vitro studies have demonstrated that hepatocytes express components of the NFkB pathway in human and rodents [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism by which METH induces inflammation in astrocyte cells remains unclear. It is well known that inflammation is the tight modulation of nuclear factor-jB (NF-jB) signal by inducing the degradation of inhibitory jBa (IjBa) and the nuclear translocation of p65 subunit, causing the release of inflammatory cytokines or cytotoxic productions [22][23][24]. Therefore, the inhibition of NF-jB signaling may be beneficial in protecting from the inflammation response and death of cells.…”
Section: Introductionmentioning
confidence: 99%